Translation Problems and Techniques of Key Legal–Commercial Terms in Abbott’s Purchase Order - Taufik Nur Hidayat; Nur Hasyim; Supriatnoko Supriatnoko; Darul Nurjanah (Jurnal Lingua Idea, 2025)
This study analyzes the translation problems and translation quality of key legal–commercial terms in Abbott’s Purchase Order Terms and Conditions, a bilingual corporate document used in international business. Adopting a qualitative descriptive approach, 60 legally significant terms were examined using Spradley’s componential analysis to identify problem types, Molina and Albir’s (2002) taxonomy to classify translation techniques, and Nababan et al.’s (2012) Translation Quality Assessment model to evaluate accuracy, acceptability, and readability, supported by expert validation. The results showed that major translation problems include system-bound non-equivalence, ambiguity, under-translation, modality errors, and terminology inconsistency, largely caused by conceptual gaps between English common-law terminology and Indonesian civil-law concepts. Calque emerged as the most frequently used technique, often producing unnatural, unclear, or misleading renderings, while established equivalents resulted in more accurate and acceptable translations. Literal and calque frequently weakened legal precision by reproducing surface linguistic forms without conveying the functional legal effects of the source text. Overall, the study concludes that translating legal–commercial terminology requires linguistic competence, comparative legal knowledge, and consistent terminology management. The findings highlight the need for improved translation practices, more rigorous post-editing of machine-assisted output, and closer collaboration between translators and legal experts to ensure clarity, accuracy, and enforceability in bilingual corporate documents.